Respuesta :

s=tT/T-r

Hope this helped

The equation T(r + s) = rs is simplified as s = Tr / (r - T).

What is the solution to the equation?

The distribution of weights to the variables involved that establishes the equilibrium in the calculation is referred to as a result.

Making anything easier to accomplish or comprehend, as well as making it less difficult, is the definition of simplification.

The equation is given below.

T(r + s) = rs

Solve the equation for s, then we have

Tr + Ts = rs

rs - Ts = Tr

s(r - T) = Tr

s = Tr / (r - T)

Thus, the equation T(r + s) = rs is simplified as s = Tr / (r - T).

More about the solution of the equation link is given below.

https://brainly.com/question/545403

#SPJ5